A spongy Rhizophora mucronata derived ultra-high surface area activated carbon for high charge density supercapacitor device. (June 2022) - Siddiqa, Aisha; Sherugar, Prajwal; Nagaraju, D.H.; Padaki, Mahesh
Abstract: Biomass-derived activated carbons are considered promising materials for numerous commercial applications owing to their outstanding properties. The current work demonstrates a successful two-step synthesis strategy, resulting in the conversion of spongy Rhizophora mucronata fruit into an ultra-high surface area activated carbon for energy storage. The best material chosen upon optimization, displayed a very large specific surface area of ~3347 m 2 /g due to the combined effect of the KOH activation mechanism as well as the liberation of oxygen from the air sacs of aerenchyma present in the biomass. This ultra-high surface area activated carbon exhibited a specific capacitance of 282 F/g at 0.5 A/g in three-electrode configuration with a 6 M KOH electrolyte. Owing to such a huge surface area, a two-electrode symmetric device MGAC-3//MGAC-3 was fabricated that revealed a specific capacitance of 200 F/g at 0.5 A/g. A remarkable energy density of 27.52 Wh/kg at a power density of 500 W/kg was achieved for the as-fabricated symmetric device which makes it a promising high charge density electrode material. Notable stability was achieved with Coulombic efficiency of 99.2% with capacitance retention of 88.3% after 20, 000 prolonged charge-discharge cycles. Graphical abstract: Unlabelled Image Highlights: Herein we report an ultra-high specific surface area (3347 m 2 /g) activated carbon. The unique property of air sacs in Rhizophora mucronata fruit aids to create highly porous carbon. The fabricated symmetric device achieved a specific capacitance of 200 F/g at 0.5 A/g with 6 M KOH electrolyte. Superior energy density 27.52 Wh/kg and 14.72 Wh/kg at power density 500 W/kg and 20.01 kW/kg respectively were accomplished. The material exhibited Coulombic efficiency of 99.2% with 88.3% capacitance retention after 20, 000 cycles.